Quantification of thioacetamide-induced liver necrosis using fractal analysis - Milosavljević, Jovan; Zaletel, Ivan; Puškaš, Nela (Medicinski podmladak, 2018)
Introduction: The liver is particularly susceptible to the toxicity from numerous chemical agents because of its central role in the detoxification. Thioacetamide-induced liver injury is used as an animal model of acute hepatic failure. Fractal analysis is a mathematical method used to measure the complexity of natural objects and can be represented solely using one parameter – the fractal dimension. Aim: The aim of this study was to investigate whether fractal analysis could be used to determine and quantify the hepatotoxic effect of thioacetamide on rat liver. Material and methods: Adult male Wistar rats were randomized into two groups: experimental group undergoing treatment with thioacetamide (600 mg/kg i.p.) and control group undergoing treatment with saline. Tissue samples were stained with hematoxylin & eosin (H&E) and Masson’s trichrome protocol. Graphic processing and fractal analysis were performed using the ImageJ software. Two fractal dimensions were calculated: the fractal dimension of liver parenchyma (Dpar) and the fractal dimension of liver sinusoids (Dsin). Results: Dpar value was significantly lower in the experimental group as compared to the control, in both samples stained with H&E and Masson’s trichrome (p < 0.0001). Dsin value was significantly higher in the experimental group in tissue samples stained with H/E (p < 0.0001). Additionally, we calculated the Dpar/Dsin ratio, which was significantly lower in the experimental group in tissue samples stained with both H&E and Masson’s trichrome protocol. Conclusion: These results show that fractal analysis could prove as a useful, easy and low-cost method in the detection and quantification of thioacetamide-induced liver necrosis. Key words: hepatic encephalopathy, toxicity, liver lobule, box-counting